2015
DOI: 10.1002/nau.22808
|View full text |Cite
|
Sign up to set email alerts
|

Bladder wall thickness in women with symptoms of overactive bladder and detrusor overactivity: Results from the randomised, placebo-controlled shrink study

Abstract: There was no consistent effect of solifenacin on BWT in women with OAB/DO, despite improvements in efficacy endpoints. This study suggests that routine clinical assessment of BWT with TVUS for monitoring the effects of OAB/DO treatment is not clinically useful. Neurourol. Urodynam. 35:819-825, 2016. © 2015 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 22 publications
1
19
1
1
Order By: Relevance
“…The results of this study are in conflict with those of the recent RCT of Solifenacin . However, in that study, a urodynamic finding of DO was required for inclusion, while an increased BWT was not necessary.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…The results of this study are in conflict with those of the recent RCT of Solifenacin . However, in that study, a urodynamic finding of DO was required for inclusion, while an increased BWT was not necessary.…”
Section: Discussioncontrasting
confidence: 75%
“…Changes are most pronounced for patients with increased BWT (≥5 mm), with reductions from a baseline of less than 5 mm being unlikely . For example, in a recent large RCT of women with DO, with mean baseline BWT of around 5 mm, no differences were observed following anticholinergic treatment …”
Section: Introductionmentioning
confidence: 99%
“…However, in the SHRINK study only 50% of women had a baseline BWT value above 5.0 mm, which is considered the preferred BWT threshold value to define the presence of DO compared to healthy subjects . Consistently in a subgroup analysis of the SHRINK study, patients with a baseline BWT >5 mm showed numerically greater reductions in BWT values . These data are also supported by a multicenter randomized placebo controlled double blind trial to evaluate whether tolterodine can reverse the increased BWT in female patients with OAB.…”
Section: Discussionmentioning
confidence: 70%
“…However, conflicting results were observed in some prospective studies evaluating BWT to diagnose DO or as a proxy of antimuscarinic treatment. In the SHRINK trial, Robinson et al exclusively evaluated the possible role of BWT as a proxy of solifenacin efficacy in female patients with OAB . The study was not designed to evaluate the diagnostic accuracy of BWT versus DO considering that no control group (patients without a diagnosis of DO) was included in the trial and no post‐treatment urodynamic examination was performed to test the persistence of DO .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation